In vivo dissection of behaviorally-relevant neuronal relaxin signaling pathway - Zanini, Rebeca (2023)
Relaxin-like peptides (relaxins) belong to the insulin-like family of peptides. Instead of acting via receptor tyrosine kinases as insulin and insulin-like growth factors do, relaxins typically exert their biological effects by binding to G protein-coupled receptors. The relaxin signaling pathway is found both in invertebrates and vertebrates, including humans, and plays important roles in the reproductive, circulatory, skeletal, renal, and nervous systems. The therapeutic potential of human relaxins, for instance, are being explored due to their vasodilator, antifibrotic, and antidepressant properties. However, the biology of relaxin receptors is not fully understood. Here, our primary aim is to identify new conserved regulatory mechanisms of relaxin receptor activity. For this, we are using a relaxin-receptor-dependent Drosophila phenotype to screen for new relaxin pathway components and regulators. In Drosophila, lack of the relaxin-like peptide, Dilp8, or its neuronal G protein-coupled receptor, Lgr3, compromises the formation of the puparium, a sort of cocoon generated by the larva from its own external cuticle to protect itself from desiccation and predators during metamorphosis. During puparium formation, or pupariation, the cuticle is actively remodeled by stereotyped muscle contractions and then hardened enzymatically. Reduced Lgr3 receptor signaling in six ventral nerve cord interneurons leads to abnormally shaped puparia, a phenotype that can be easily, cheaply, and quickly scored by eye at the same time that it is highly informative about the integrity of the Dilp8-Lgr3 relaxin signaling pathway, the presence and integrity of the critical Lgr3-positive interneurons, and the complex behavior they mediate. Taking advantage of this, we are performing a large cell-typespecific RNAi screen in vivo using a UAS-inducible RNAi stock collection for genes expressed in the central nervous system. In this presentation we will provide an update on the ˜1500 genes screened up to now and an initial dissection of the candidate hits identified.